Assistive technologies for the visually impaired undergraduates of the University of Colombo - Lankathilake, M.A. (Library, University of Colombo, Sri Lanka, 2018)
Visually impaired undergraduates encounter difficulties in accessing information when compared to their peers. With the development of information technology number of assistive technologies and devices have become popular among the visually impaired than traditional methods. This study is planned with the objective of identifying assistive technologies for the resource center for visually impaired. A literature review and focus group discussions were conducted to identify the suitability of assistive technologies. Focus groups consisted of visually impaired academics, library and information professionals and visually impaired undergraduates. Closed-Circuit Television (CCTV) (83%), audio books (75%), screen magnifier (58%) and screen readers (50%) were identified as highly used assistive devices. Although the braille books are recognised as traditional resources they were also identified as important. In addition to the above devices, braille keyboards, braille note-takers, braille displays and speech synthesizers were identified as assistive devices through the literature survey. According to the discussions with focus group audio books, screen magnifiers, braille displays, braille books and screen readers were identified as extensively used devices. The resource center for the visually impaired at the main library is equipped with braille reader, DAISY digital talking book players and portable digital video magnifiers. According to findings it could be stated that resources and services available in the resource center for visually impaired in University of Colombo are not sufficient to fulfil the needs of the visually impaired undergraduates. Therefore it is recommended to acquire audio book collections covering diverse subject areas, computers with screen reading facility, braille keyboards, screen magnifiers and important braille books to minimize the difficulties in accessing information by visually impaired undergraduates.
Keywords: assistive technologies; University of Colombo; visually impaired undergraduates